Satisfaction with the government as a mediator in relationship between online news gratification and election voting choices - Alivi, Mumtaz Aini (2019)
Media plays an important role in shaping a country’s democracy by feeding the public with relevant and purposeful information. Usage of media is crucial for the public before they could make decisions about the political landscape of the country by voting. In recent years, online news sites have played a key role in influencing vote choice, the hallmark of democracy. Likewise, the emergence of online news is recognized for its importance in shaping the political discourse in Malaysia. However, previous studies on online news have not dealt with the relationship between online news gratifications and vote choice. Studies on online news are scarce and research on the impact of online news gratification on vote choice in Malaysia is inconclusive. Therefore, the general objective of this study is to investigate the relationship between online news gratifications in determining vote choice. Specifically, this research aims to understand the motive for using online news and the gratification sought and obtained from it in influencing vote choice. The study is guided by the combination of Uses and Gratification and Rational Choice theory. Using the quantitative approach, the study was carried out by engaging a total of 700 respondents who were registered voters living in Klang Valley. Apart from using purposive sampling, snowball sampling was also employed to select respondents from different races. The data was analyzed using IBM SPSS for descriptive statistic and Structural Equation Modelling (SEM) using SmartPLS for modelling. The finding revealed that online news plays a vital role in shaping the opinion of citizens which is translated through vote choice. In addition, the study also indicated that the motive to use online news and the gratification obtained are significant in determining vote choice. However, gratification sought was found to be insignificant in determining vote choice. Meanwhile, satisfaction with the government were also found as an important indicator that determines the relationship between online news gratification and vote choice. This study provides crucial practical implications that can benefit the media industry. In terms of policy implication, government can capitalize on the effectiveness of the online medium to reach the public and rationalize major policy decisions. This study also contributes to theory development by adding the element of satisfaction with government as a mediating construct in the theoretical framework. In terms of methodological implication, this study contributes to the literature by expanding the usage of PLS-SEM analysis in social science, generally and mass communication field, specifically.